Antidepressant‐like Effects of Degraded Porphyran Isolated from Porphyra haitanensis. Issue 9 (14th April 2021) - Yi, Li‐Tao; Zhang, Man‐Man; Cheng, Jie; Wan, Hui‐Qi; Li, Cheng‐Fu; Zhu, Ji‐Xiao; Zhang, Qiu‐Ping; Liu, Qing; Xu, Guang‐Hui
Abstract : Introduction: Degraded porphyran is a bioactive polysaccharide extracted from Porphyra haitanensis ( P. haitanensis ). According to the previous studies, it produced anti‐inflammatory activity, but little is known about its effects on depression. Methods and Results: As inflammation is one of the critical factors involved in the development of depression, this study aims to elucidate the potential antidepressant‐like effects of degraded porphyran. The results show that acute porphyran treatment decreased the immobility time in despair tests. In addition, subchronic porphyran administration reverses depressive‐like behaviors in lipopolysaccharide (LPS)‐treated mice. Meanwhile, porphyran inhibits NF‐κB/NLRP3 signaling, proinflammatory cytokine release, and microglial activation in the hippocampus. Moreover, chronic porphyran treatment activates hippocampal brain derived neurotrophic factor (BDNF)/TrkB/ERK/CREB signaling pathway in chronic unpredictable mild stress (CUMS) in mice. As a result, neurogenesis and spinogenesis are maintained. Conclusions: The findings of the present study indicate that degraded porphyran intake provides a potential strategy for depression treatment, which is mediated by the inhibition of neuroinflammation and the enhancement of neurogenesis and spinogenesis in the central nervous systems. Abstract : Porphyran reverses neuroinflammation via inactivation of microglial NF‐κB/NLRP3 and proinflammatory cytokine release. Meanwhile, porphyran attenuates impairments of hippocampal neurogenesis and spinogenesis by activating BDNF/TrkB/ERK/CREB signaling pathway.